Digitalization and Public Value Co-Creationin Public Sector Organizations : The Citizens as Co-Creators - Chinedu Ofoma (Institutiones Administrationis, 2024)
Public value co-creation emerged as a perspective that takes public service delivery beyond effectiveness and efficiency to the services that involve different actors which meet the citizens’ satisfaction and expectation. This development has necessitated the adoption of several strategies by governments aimed at achieving this goal. Arising from this understanding, this paper’s objective rests upon the exploration of the correlation between digitalization and public value co-creation in public sector organizations viewing the citizens as co-creators. Utilizing secondary sources of data, the paper compellingly argues that the citizens could participate more actively and effectively in digitalization driven public value co-creation in public sector organizations. However, it is highlighted in the study that digital divide is a potential obstacle which could undermine the role of citizens towards digitalization driven public value co-creation in public sector organizations. As a panacea, the paper recommends for decentralization of digital governance so as to provide majority of the citizens (especially those at the remote areas) the opportunity to participate in the public value co-creation processes.